2012
DOI: 10.1038/ni.2208
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor RORα is critical for nuocyte development

Abstract: Nuocytes are essential in innate type-2 immunity and contribute to the exacerbation of asthma responses. Here we show that nuocytes arise in the bone marrow and differentiate from common lymphoid progenitors, which makes them distinct new members of the lymphoid lineage. Nuocytes required interleukin 7 (IL-7), IL-33 and Notch signalling for development in vitro. Double negative 1 (DN1) and DN2 pro-T-cell progenitors maintained nuocyte potential in vitro, although the thymus was not essential for nuocyte develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
601
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 531 publications
(624 citation statements)
references
References 50 publications
17
601
1
5
Order By: Relevance
“…Downstream of this Id2-dependent progenitor appears to lie an ILC precursor that is dependent on the transcription factor promyelocytic leukaemia zinc finger protein (PLZF) (encoded by Zbtb16), and this progenitor gives rise to ILC1, ILC2, and ILC3, but not classical natural killer (NK) cells or LTi (30) (Figure 1 The timing and duration of Notch signals has also been shown to be critical for lymphoid differentiation and is required for the generation of mouse ILC2 from CLPs in vitro (27). Notch signaling is also important for the generation of human ILC2, and the use of a tuneable intracellular domain of Notch1 indicated that low levels of Notch signaling lead to T-cell TRANSATLANTIC AIRWAY CONFERENCE development, whereas high concentrations lead to ILC2 differentiation (31).…”
Section: Ilc Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Downstream of this Id2-dependent progenitor appears to lie an ILC precursor that is dependent on the transcription factor promyelocytic leukaemia zinc finger protein (PLZF) (encoded by Zbtb16), and this progenitor gives rise to ILC1, ILC2, and ILC3, but not classical natural killer (NK) cells or LTi (30) (Figure 1 The timing and duration of Notch signals has also been shown to be critical for lymphoid differentiation and is required for the generation of mouse ILC2 from CLPs in vitro (27). Notch signaling is also important for the generation of human ILC2, and the use of a tuneable intracellular domain of Notch1 indicated that low levels of Notch signaling lead to T-cell TRANSATLANTIC AIRWAY CONFERENCE development, whereas high concentrations lead to ILC2 differentiation (31).…”
Section: Ilc Precursorsmentioning
confidence: 99%
“…In contrast to the more generic ILC commitment factors, the transcription factor RORgt (encoded by Rorc) has been identified as a key regulator of ILC3 cells (10,(32)(33)(34), and RORa has been identified as a key determinant of ILC2 differentiation (27,35). However, even here there is overlap of transcription factor use, with Th17 cells requiring RORgt, and RORa also playing a subordinate role in Th17 cell development.…”
Section: Committed Ilc2mentioning
confidence: 99%
See 1 more Smart Citation
“…These cells are CD90 (Thy1) + , Sca1 + , CD25 (IL-2Rα) + , CD127 (IL-7Rα) + , and IL-33Rα + . The development of group 2 ILCs is largely dependent on the transcription factors Id2 [12], GATA-3 [15], and RORα [16]; as well as on γc signaling [12,14]. Although the cytokines produced by group 2 ILCs are similar to Th2 cytokines, ILCs are not activated by antigen receptor stimulation and they are widely distributed within various tissues [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, IL-7 is required for the development of all ILC populations with the exception of conventional NK cells and recently described ILC1 populations (Klose et al 2014). By contrast, the retinoic acid receptor-related RORa has been shown to be a key TF solely for ILC2 development as in Rora mutant mice numbers of ILC2, but not other ILC populations, are markedly reduced (Halim et al 2012;Wong et al 2012). Additionally, CLP require IL-33 and Notch signaling to develop into ILC2 in vitro.…”
Section: Development and Ontogeny Of Ilc2mentioning
confidence: 99%